USULAN SOLUSI MENGATASI MARAKNYA PENGGUNAAN SOFTWAFIE ILEGAL DALAM SISTEM INFORMASI BERBASIS KOMPUTER DI INDONESIA - Andriana Victoria; Firdhausyia Rahmani; Irma Nurmalasari; Rika Athena; Yoane Theresia; Vera Yuanita (Center for Economic Studies Universitas Katolik Parahyangan, 2008)
Software piracy, otherwise known as copyright infringement, is one of several forbidden actions that may threat to the technological advances. This can be done by copying, downloading, sharing, selling, or installing multiple copies onto personal or work computers. The most important cause is habitual society using commercial .software even though their purchasing powers are low. This paper describes some solutions to keep level of software piracy down and which parties required to successfully implement those solutions.